SYNTHESIS AND ANTIMICROBIAL ACTIVITY OF SOME 3-ARYL-5-IMIDAZOLYL-2-PYRAZOLINES: Life Sciences-Chemistry - MOHAMMAD ALI EBRAHIMZADEH; FERESHTEH POURMORAD (International Journal of Life Science and Pharma Research, 2022)
Pyrazolines are well known and important nitrogen containing ﬁve membered heterocyclic compounds. Considerable interest has been focused on the pyrazoline structure, which has been known to possess a broad spectrum of biological activities. Reaction of α,β-unsaturated aldehyde and/or ketones with hydrazines is one of the most popular method for the preparation of 2- pyrazolines. In this study a new series of 3-aryl-5-imidazolyl-2-pyrazolines have been synthesized and evaluated for their antibacterial and antifungal activities. Desired chalcones were prepared by condensing appropriate acetophenones with substituted imidazole-5- carboxaldehyde. Reaction of chalcones with phenyl hydrazine, hydrazine hydrate or thiosemicarbazide gave desirable pyrazolines. Compounds with thiosemicarbazide and para hydroxyl substitution showed potent antibacterial activity. This is consistent with the observation made earlier by other researchers. The compounds did not show any antifungal activity.